Craniofacial sensations induced by transient changes of barometric pressure in healthy subjects – A crossover pilot study. (11th March 2021) - Funakubo, Megumi; Sato, Jun; Mizumura, Kazue; Suzuki, Norihiro; Messlinger, Karl
Background: Changes in atmospheric pressure are suggested to trigger headaches. This pilot study was made to determine craniofacial sensations accompanying short phases of changing barometric pressure. Methods: In a crossover design, 15 adult healthy subjects were exposed in a climate chamber to 8 min phases of barometric pressure lowering by 0, 20 and 40 hPa. The subjects rated their sensations of ear pressure, head compression and the occurrence of headache every minute on a visual analogue scale (VAS, range 0–10). Pulse rate was recorded as a parameter for autonomic functions. Results: Nearly all subjects experienced ear pressure and half of them compression of their head at variable degrees. These sensations started in most subjects during the phase of lowering barometric pressure and increased to an average rating of about 3 VAS when returning to ambient atmospheric pressure. Heart rate slightly decreased during this phase. Three subjects reported mild to moderate headache for various durations within these phases. Conclusions: Changes in barometric pressure can be associated with sensations of ear pressure and head compression and may trigger headaches. The generation of these sensations is discussed with regard to convergent trigeminal innervation of the ear, the paranasal sinuses and the cranial meninges.